2020
DOI: 10.3389/fphys.2020.01041
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the Influence of Genetics on Breast Muscle Myopathies in Broiler Chickens

Abstract: This report provides the first estimates of the genetic basis of all key breast muscle myopathies (BMM) in broiler chickens [Deep pectoral myopathy, wooden breast, white striping and spaghetti breast] and their relationship with body weight and breast yield. Data from a pure bred high yielding commercial broiler line were analysed to estimate the genetic parameters using a multivariate animal model with the appropriate fixed effects and permanent environmental effect of the dam. Heritabilities of the BMM range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 70 publications
(105 reference statements)
2
30
0
Order By: Relevance
“…In contrast, a previous study compared the differences in selection history for increased breast yield between 2 purebred commercial broiler lines with breast yields of 21% and 29%, the results indicated a very low heritability (the ratio between the additive genetic variance and the phenotypic variance) for WB, which suggests a non-genetic basis explaining the variation in WB incidence ( Bailey et al., 2015 ). A similar conclusion was drawn in another study conducted by the same group with a pure-bred commercial broiler line ( Bailey et al., 2020 ). The inconsistent results may be due to the differences in the sample size, the genetic lines that were used, the technique used to evaluate the genetic contribution, etc.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, a previous study compared the differences in selection history for increased breast yield between 2 purebred commercial broiler lines with breast yields of 21% and 29%, the results indicated a very low heritability (the ratio between the additive genetic variance and the phenotypic variance) for WB, which suggests a non-genetic basis explaining the variation in WB incidence ( Bailey et al., 2015 ). A similar conclusion was drawn in another study conducted by the same group with a pure-bred commercial broiler line ( Bailey et al., 2020 ). The inconsistent results may be due to the differences in the sample size, the genetic lines that were used, the technique used to evaluate the genetic contribution, etc.…”
Section: Discussionsupporting
confidence: 87%
“…Otherwise, the distinctive phenotype of SM has been also thought to be associated with an excessive build-up of lactic acid in the muscle, leading to the inhibition of protein synthesis regulating collagen development (Anton et al, 2019). On the other hand, contrarily to what previously observed for WS and WB (Radaelli et al, 2017), it must be pointed out that the low heritability levels of SM may indicate the impact of non-genetic factors on the variance of the myopathy traits (Bailey et al, 2020). Indeed, the weak correlation between the incidence of SM condition and animals' growth rate, age, and weight at slaughter might hint at other "contributing factors" related to slaughtering operations (e.g., scalding, de-feathering, chilling, post-mortem deboning time and technology, etc.)…”
Section: Current Challenges and Potential Future Developmentsmentioning
confidence: 76%
“…Data concerning the incidence rates of SM condition are limited and sometimes contradictory, likely due to both the variation of classification criteria among the abattoirs and the complication related to the concurrent presence of other myopathies within the same muscle, since SM can be comorbid with WB and, more likely, with WS (Baldi et al, 2018;Bailey et al, 2020). However, an Italian survey carried out on 16,000 breasts reported that around 21% of samples were affected by SM (Baldi et al, 2020a), while a Brazilian study evaluated about 10% of SM fillets on a total of 5,580 breasts (Montagna et al, 2019).…”
Section: Up-to-date Knowledge Morphological Characteristics and Incidence Levelsmentioning
confidence: 99%
“…Genetic studies have shown heritability estimates ranging from 0.18 to 0.65 for WS ( Bailey et al, 2015 , 2020 ; Alnahhas et al, 2016 ; Lake et al, 2021 ) indicating an important genetic component influence on the occurrence of WS in broilers. Furthermore, positive genetic correlations between WS and body weight (0.23) and breast yield (0.31) traits, as well as with other myopathies, such as wooden breast (0.74) and deep pectoral myopathy (0.34) have also been found ( Bailey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have shown heritability estimates ranging from 0.18 to 0.65 for WS ( Bailey et al, 2015 , 2020 ; Alnahhas et al, 2016 ; Lake et al, 2021 ) indicating an important genetic component influence on the occurrence of WS in broilers. Furthermore, positive genetic correlations between WS and body weight (0.23) and breast yield (0.31) traits, as well as with other myopathies, such as wooden breast (0.74) and deep pectoral myopathy (0.34) have also been found ( Bailey et al, 2020 ). Recently, many genes have been associated with the occurrence of myopathies in chickens ( Zambonelli et al, 2016 ; Beauclercq et al, 2017 ; Zampiga et al, 2018 ; Marchesi et al, 2019 ; Lake et al, 2021 ), and the identification of specific biomarkers can help to accurately assess the effect of genetics, environment, or management conditions in improving or aggravating the WS myopathy in broilers ( Beauclercq et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%